Pengaruh Teknik Skarifikasi Fisik dan Media Perkecambahan terhadap Daya Berkecambah Benih Pala (Myristica fragrans) - Dwi Gery Febriyan; Eny Widajati (Buletin Agrohorti, 2015)
The objective of this experiment is studying the effect of physical scarification of nutmeg seed coat and germination media to accelerating germination rate and enhancing nutmeg seed viability. This experiment was conducted in December 2013 until May 2014 at Leuwikopo Experimental Field’s green house and Seed Laboratory  of  Agronomy  and  Horticulture  Department,  Faculty  of  Agriculture,  Bogor  Agricultural University. This experiment was using factorial randomize complete block design with 3 replications. The first factor was physical scarification on the seed coat with three levels: without scarification, one hole scarification on seed’s base, and two holes scarifications on seed’s base. The Second factor was the seed germination substrate that consist of sand, charcoal of husk rice, and mixture of sand and compost 1:1 (v/v). The results showed that two holes physical scarification could enhance germination process according to the earlier appearance of roots and shoot. Sand as the germinating substrate was observed as a better substrate according to the parameters of germinating potency and shoot height. Two holes physical scarification treatment which was sowed in sand substrate showed the increase of lateral root number into 6 lateral roots. Nutmeg seedling growth from sand substrate seedling showed a better growth than the charcoal of husk rice substrate seedling by evaluating these parameters on stem diameter, seedling’s height, amount of leaves, canopy’s width, and leaves colour.